ACUPRESSURE AS COMPLEMENTARY AND ALTERNATIVE THERAPY FOR REDUCING PAIN INTENSITY: A NARRATIVE REVIEW - Enggal Hadi Kurniyawan (Faculty of Nursing, Universitas Jember, 2016)
Medications used to treat or reduce the symptoms of pain usually have side effect. Acupressure is a complementary and alternative therapy that can be used to reduce pain intensity and has no side effect. This narrative review described acupressure as an alternative therapy in reducing acute and chronic pain intensity. This narrative review included 25 articles published between 2006 and 2016 by using google scholar search engine. Keywords used to find the articles were acupressure and pain. Most of articles used in this narrative review concluded that acupressure effectively reduces acute pain and chronic pain intensity in the several kinds of diseases. Acupressure has many functions for the body's health especially to reduce acute pain and chronic pain intensity. Pain occurs because of an imbalance in the flow of qi energy in the body. Acupressure will balance the flow of qi energy body that will reduce pain intensity and cure the illness. The balance of qi energy will improve the vitality and body health thus protects from various diseases.